Tiger Dance: Transformation and Cultural Property Rights Discourse in Kerinci, Indonesia - Febriyandi YS, Febby; Swastiwi, Anastasia Wiwik (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2024)
This article aims to answer why the tiger dance in Kerinci Regency, Jambi Province, has not developed widely despite being preserved for more than 30 years and becoming a popular dance in Jambi Province. Qualitative research methods were used to carry out this study. In-depth interviews and uninvolved observation of the artists’ activities were used to collect the data. The analysis focused on the development of the tiger dance and the preservation discourse created by the artists and residents of Pulau Tengah Village. This study discovered that the extinct Ngagoah Imo ritual was transformed into the tiger dance. The “tiger man” myth, which the Kerinci people still hold dear, forms the basis of the tiger ritual and dance. Initially, the tiger dance was not sacred but was made sacred due to encouragement from various parties. Because of its uniqueness, the tiger dance soon became popular in Jambi and became a cure for the longing of the Kerinci people for the Ngagoah Imo ritual. Realizing the potential of tiger dance as an economic resource and as Kerinci’s regional identity, the artists then created a discourse of property rights over tiger dance. They prohibited other villagers from learning or imitating it. This discourse is slowly making tiger dance endangered because it is only controlled by a small group of artists. Such a discourse on cultural property rights needs to be straightened out. Apart from being contrary to the dynamic character of Malay culture, it is also contrary to various principles of cultural preservation.